Effect of Curcumin Nanoemulsion on Brain Cell Development, Locomotor Function, and Mortality of Zebrafish Larvae Model of Gestational Diabetes Mellitus - Subandi, Subandi; Azahra, Mutiara Syifa; Ovinery, Amarsya; Akhmalia, Qorry' Afyu; Asih, Aliyah Tresna; Sulistomo, Hikmawan Wahyu; Nurdiana, Nurdiana; Wiyasa, I Wayan Arsana (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Introduction. Gestational diabetes mellitus (GDM) is glucose intolerance in pregnancy due to reduced ability of pancreatic beta cells to produce insulin, causing oxidative stress that triggers various complications such as brain apoptosis to locomotor disorders and decreased head size which has an impact on mortality rates. Pharmacological treatment of GDM has side effects that risk affecting fetal development. Therefore, curcumin as a herbal medicine can be an option for GDM treatment because it can increase insulin sensitivity by activating the peroxisome proliferator-activated receptor-gamma (PPAR-gamma) receptor. Methods. Post Test Only Control Group Design was used in this experimental study which was tested on each research variable consisting of 25 zebrafish embryos divided into 5 treatment groups consisting of a negative control, a positive control exposed to 3% glucose, and a diabetic group given curcumin nanoemulsion with three different doses (0.3125 μg/ml, 0.625 μg/ml, 1.25 μg/ml). One Way ANOVA and Post Hoc Tukey tests were used to analyze the data from this study. Results. P value from One Way ANOVA test p=0.024 for brain apoptosis, p=0.00 for locomotor ability, p=0.04 for head size, and p=0.006 for mortality rate. Turkey Post Hoc test showed significant differences in the control and 3% glucose + 0.625 µg/ml curcumin nanoemulsion groups (p<0.05). Conclusion. Curcumin nanoemulsion therapy has an effect on decreasing brain apoptosis, increasing locomotor, inhibiting the decrease in head size, and decreasing the mortality rate in zebrafish with gestational diabetes. The most effective dose of curcumin nanoemulsion is 0.625 µg/ml.